Impact of industrial structure and soil exposure on the regional variations in pulmonary nontuberculous mycobacterial disease prevalence. Issue 2 (June 2016) - Hamada, Satoshi; Ito, Yutaka; Hirai, Toyohiro; Murase, Kimihiko; Tsuji, Takahiro; Fujita, Kohei; Mio, Tadashi; Maekawa, Koichi; Fujii, Takashi; Ono, Shigeki; Nishimura, Takashi; Hayashi, Akihiko; et al.
Abstract: Objective/background: The prevalence of pulmonary nontuberculous mycobacterial (pNTM) disease, including Mycobacterium avium complex (MAC), varies widely according to geographic region. However, the factors that influence regional variations in pNTM disease prevalence remain unknown. This study was undertaken to examine whether environmental or occupational factors or host traits could influence regional variations in pNTM disease prevalence. Methods: We collected laboratory data on pulmonary tuberculosis (pTB) and pNTM from two hospitals in the West Harima area of Japan and five hospitals in Kyoto City, Japan from 2012 to 2013. We estimated microbiological pNTM disease prevalence by multiplying all pTB cases in each area with the ratio of pNTM cases and pTB cases at the survey hospitals in each area. We administered a standardized questionnaire to 52 patients and 120 patients with pulmonary MAC (pMAC) disease at Ako City Hospital and Kyoto University Hospital, respectively. Results: The estimated prevalence of microbiological pNTM disease in the West Harima area (85.4/100, 000 population-years) was significantly higher than that observed in Kyoto City (23.6/100, 000 population-years; p  < .001). According to multiple logistic regression analysis, in Ako City Hospital, primary (activities directly related to natural resources) and secondary industries (construction, mining, and manufacturing primary industry produce; odds ratio [OR] = 4.79; 95% confidence interval [CI] = 1.49 − 14.0; p  = .007) and soil exposure (OR = 13.6; 95% CI = 4.94 − 45.26; p  < .001) were associated with pMAC disease. Conclusion: Environmental factors, both industrial structures associated with occupational dust and environmental soil exposure, could influence the regional variations in pNTM disease prevalence.